s*s-12s+12=0

Simple and best practice solution for s*s-12s+12=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for s*s-12s+12=0 equation:


Simplifying
s * s + -12s + 12 = 0

Multiply s * s
s2 + -12s + 12 = 0

Reorder the terms:
12 + -12s + s2 = 0

Solving
12 + -12s + s2 = 0

Solving for variable 's'.

Begin completing the square.

Move the constant term to the right:

Add '-12' to each side of the equation.
12 + -12s + -12 + s2 = 0 + -12

Reorder the terms:
12 + -12 + -12s + s2 = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -12s + s2 = 0 + -12
-12s + s2 = 0 + -12

Combine like terms: 0 + -12 = -12
-12s + s2 = -12

The s term is -12s.  Take half its coefficient (-6).
Square it (36) and add it to both sides.

Add '36' to each side of the equation.
-12s + 36 + s2 = -12 + 36

Reorder the terms:
36 + -12s + s2 = -12 + 36

Combine like terms: -12 + 36 = 24
36 + -12s + s2 = 24

Factor a perfect square on the left side:
(s + -6)(s + -6) = 24

Calculate the square root of the right side: 4.898979486

Break this problem into two subproblems by setting 
(s + -6) equal to 4.898979486 and -4.898979486.

Subproblem 1

s + -6 = 4.898979486 Simplifying s + -6 = 4.898979486 Reorder the terms: -6 + s = 4.898979486 Solving -6 + s = 4.898979486 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + s = 4.898979486 + 6 Combine like terms: -6 + 6 = 0 0 + s = 4.898979486 + 6 s = 4.898979486 + 6 Combine like terms: 4.898979486 + 6 = 10.898979486 s = 10.898979486 Simplifying s = 10.898979486

Subproblem 2

s + -6 = -4.898979486 Simplifying s + -6 = -4.898979486 Reorder the terms: -6 + s = -4.898979486 Solving -6 + s = -4.898979486 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + s = -4.898979486 + 6 Combine like terms: -6 + 6 = 0 0 + s = -4.898979486 + 6 s = -4.898979486 + 6 Combine like terms: -4.898979486 + 6 = 1.101020514 s = 1.101020514 Simplifying s = 1.101020514

Solution

The solution to the problem is based on the solutions from the subproblems. s = {10.898979486, 1.101020514}

See similar equations:

| 3+27x+15=5x+18+22x | | 0.75*18+0.25*x=17 | | 0.25x^2-5x=10 | | 4p+2q=28 | | 1+a=b-1 | | 8n-30=42 | | 4p+3q=26 | | (x+-2)(x+-2)=-25 | | 400=16t | | 12x^2+25x-7=0 | | 7m+7n= | | 2x+4x+3y= | | 79-4x=23x+19 | | (n-5)*7=35 | | (n-6)*4=40 | | -171x-9x=10x+19 | | 3x+x/2=15 | | 3a-4=0 | | 8x+3=x+38 | | x*2=8 | | 4x*5x=20 | | 4x+3x=12 | | 4x+5x=200 | | 4x+5x=10 | | 4x+5x=100 | | 4yx+5x=20 | | 4x+5y=5y | | b-8=10 | | 5x+4y=31 | | a-8=4 | | 2y-15+3y+3=24 | | z-5=r |

Equations solver categories